2016
DOI: 10.1186/s40580-016-0092-8
|View full text |Cite
|
Sign up to set email alerts
|

InGaN-based photoanode with ZnO nanowires for water splitting

Abstract: The water splitting properties of InGaN photoanodes equipped with ZnO nanowires were examined in this study. Over the solar spectrum range, the absorbance exhibited a remarkable increase due to the enhanced light absorption caused by the ZnO nanowires. By varying the ZnO nanowires length, the photo-to-current density of photoanodes was increased from 0.017 to 0.205 mA/cm2 at 1.23 V versus reversible hydrogen electrode. Consequently, the incident-photon-to-current efficiency was increased by a factor of 5.5 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The radial growth estimations indicate that (i) The colony growth when treated with pure ZnO and DE-ZnO composites are well matched with the fluorescence quenching study, with a significant synergy effect of the DE-ZnO composites showing “1 + 1 > 2” performance; and (ii) The antifungal effect of ‘pure DE + pure ZnO’ is less than the DE-ZnO composites, even less than the same amount of pure ZnO (“1 + 1 < 1”), and this phenomenon is consistent with a prior report of N dopants into hierarchically porous composites (Fig. 3 C) [ 31 , 38 ].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The radial growth estimations indicate that (i) The colony growth when treated with pure ZnO and DE-ZnO composites are well matched with the fluorescence quenching study, with a significant synergy effect of the DE-ZnO composites showing “1 + 1 > 2” performance; and (ii) The antifungal effect of ‘pure DE + pure ZnO’ is less than the DE-ZnO composites, even less than the same amount of pure ZnO (“1 + 1 < 1”), and this phenomenon is consistent with a prior report of N dopants into hierarchically porous composites (Fig. 3 C) [ 31 , 38 ].…”
Section: Resultssupporting
confidence: 90%
“…There were no significant alterations of weight or any toxicity symptoms in both the low dosage (LD)-DE-ZnO and high dosage (HD)-DE-ZnO groups. Meanwhile, when we compared with same dosage of the nanomaterials, the toxicity of DE-ZnO (2:1) is 6 times lower using oral medication and the dosage amount of DE-ZnO is 3 times higher than the SiO 2 -ZnO (Table 1 ) [ 34 , 38 ]. And the animals were sacrificed after 14 days, and their major organs including brain, heart, lung, liver, kidneys, spleen, testis or uterus were collected and weighed for males and females (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic peaks obtained for ZnO nanoparticles exist at 31.3, 33.9, 35.8, 47.1, 56.2, 62.4 and 67.6 correspond to the crystal planes of (100) (002) (101) (102) (110), (013) and (112), respectively. This result clearly indicates that ZnO nanoparticles were obtained to the ZnO hexagonal wurtzite structure [ 29 32 ]. From the results of XRD, it was confirmed that synthesis of ZnO nanoparticles was successful using both synthetic routes.…”
Section: Resultsmentioning
confidence: 93%
“…When n-type ZnO:Ga was in contact with p-type InGaN, a p-n heterojunction could be formed, yielding a band offset toward the heterointerface. 33,50,54 Due to the existence of AlGaN electron blocking layers between ZnO:Ga MW and InGaN quantum well structure, the energy band of the neighbouring ZnO:Ga barrier changes from upward to small downward bending. 18,55 Obviously, a typical staggered type-II heterojunction will be constructed between the ZnO:Ga MW and p-type InGaN film, with the energy band diagram shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…47,48 Through the appropriately designed n-ZnO/p-InGaN heterointerface, the combination of the merits of both the mature p-InGaN material and ZnO nano-/microstructures would make the as-designed low-dimensional visible light source technically and practically competitive. 33,49,50 In the present research, a new generation high-brightness green LED, which is made of a single Ga-doped ZnO microwire covered with Au nanoparticles (AuNPs@ZnO:Ga MW), a MgO buffer layer and a p-type InGaN film, was proposed and investigated experimentally. The LED showed stable green electroluminescence (EL) peaking at around 545 nm, with a spectral line-width of ∼40 nm.…”
Section: Introductionmentioning
confidence: 99%